Analisis Titik Impas Dan Batas Aman Untuk Merencanakan Laba Jangka Pendek Pada Indofood Cbp Sukses Makmur Tbk ( Khususnya Produk Indomie Goreng) - Putra, Ruddy Gustya Dwi; Apriliya, Anisa Winda; Zahra, Amanda; Huda, Syamsul (Peneliti.net, 2024)
Companies really need high profits and sales. They cannot be separated. This is in accordance with the break-even analysis used in profit planning. In profit planning using this analysis it will produce the number of sales units so that the company does not experience losses, even profits, in addition to using security points that will show sales information before losses occur. With this, the company can obtain information on the safe point of sale obtained by the company. The purpose of this study is to reveal the safety margin and break-even point obtained by Indofood CBK Sukses Makmur Tbk in the last two years. The results of this study show that the company is in good condition in the last two years, this is because the sales that occurred in 2020 and 2021 are above the break-even point and far from the safe limit, so this shows that the company will be far from losses.Break Even Point Analysis, Margin of Safety, Profit Planning.